The economics of ecology, exchange, and adaptation anthropological explorations - Wood, Donald C. (Research in economic anthropology ;, 2016)
This volume consists of three sections connected by the elucidation of differences in perspective between people and polities. The first, concentrating on ecology, serves in part to further explore the theme of climate change. It looks into aquifer usage and ecology in the Midwestern United States, farming and climate shifts in Costa Rica and in Burkina Faso, and goat herding and conservation issues in the Himalayas. The second section focuses on exchange transactions and relations in a variety of situations and settings: among Nigerian immigrant business owners in New York City, along the path of the famous Koh-i-noor Diamond from India to the Tower of London, and between dealers and buyers in illegal narcotics markets in the Eastern, Midwestern, and Pacific Northwestern USA. Finally, papers in the third section share a concern with individual and group adaptations to certain conditions of life. Offered are investigations into relations between stock brokers and professional investors in Malaysia, attempts to foster innovation in Western Japan, women's farming strategies and autonomy in Western Kenya, and alternative healing decisions and practices in Brazil.